The Effects of Service Quality, Price Perception, and Taste on Customer Satisfaction in The Food and Beverage Industry - Mohammad Reatha Deo Khairullah (Universitas Budi Luhur, 2026)
The increasing competition in the culinary industry, particularly in modern noodle restaurants, requires business actors to understand the factors that influence customer satisfaction. Customer satisfaction is not only affected by the prices offered, but also by the quality of service and the taste of the products provided to consumers. This study aims to analyze the influence of service quality, price, and taste on customer satisfaction at the Spicy Noodles XYZ restaurant in South Tangerang. This research uses a quantitative approach with a survey method through the distribution of questionnaires to 110 respondents who have visited the restaurant. The sampling technique used is purposive sampling, while data analysis is carried out using multiple linear regression analysis with the help of SPSS, which includes validity tests, reliability tests, classical assumption tests, and hypothesis tests. The research results indicate that service quality and taste have a positive and significant effect on customer satisfaction, whereas price does not have a significant effect on customer satisfaction. In addition, the simultaneous test results show that service quality, price, and taste together have a significant effect on customer satisfaction. The coefficient of determination (R²) value of 0.597 indicates that the three independent variables are able to explain 59.7% of the variation in customer satisfaction, while the remainder is influenced by other factors outside the research model.